2020
DOI: 10.31665/jfb.2020.12248
|View full text |Cite
|
Sign up to set email alerts
|

A review: potential of resveratrol and its analogues to mitigate diseases via gut microbial modulation

Abstract: The stilbenoids form a group of bioactive phenolic compounds found in various plant species whose original functions are to act as protective compounds against microbial infections and toxins. Among the stilbenoids, resveratrol is the most well-studied and has been shown to exert multiple benefits in disease prevention. The bioavailability of resveratrol is one of the major limitations in its role as a disease-prevention agent; however, it has exhibited biological activity in animals and clinical models. Gut m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Resveratrol is another famous and well-studied bioactive compound limited by oral bioavailability . One of the latest studies demonstrated that conjugating resveratrol with carbon dots (C-dots) could engender specificity toward cancer cells and improve its biological activity (Figure ).…”
Section: Phytochemicals Induce Mitochondrial Dysfunction In Cancersupporting
confidence: 62%
See 1 more Smart Citation
“…Resveratrol is another famous and well-studied bioactive compound limited by oral bioavailability . One of the latest studies demonstrated that conjugating resveratrol with carbon dots (C-dots) could engender specificity toward cancer cells and improve its biological activity (Figure ).…”
Section: Phytochemicals Induce Mitochondrial Dysfunction In Cancersupporting
confidence: 62%
“…Resveratrol is another famous and well-studied bioactive compound limited by oral bioavailability. 107 One of the latest studies demonstrated that conjugating resveratrol with carbon dots (C-dots) could engender specificity toward cancer cells and improve its biological activity (Figure 4). 108 C-dots are nanoscale carbonaceous particles with a particle size smaller than 10 nm, and they have emerged as a powerful theranostic platform because of their biocompatibility and low toxicity and could be employed in cell targeting.…”
Section: Phytochemicals Impair Mitochondria To Achieve Cancer Preventionmentioning
confidence: 99%